2014
DOI: 10.1002/2014gl059498
|View full text |Cite
|
Sign up to set email alerts
|

Closing the transport budget of the Florida Straits

Abstract: Closing the mean mass budget of the Florida Straits is fundamental to understanding the source waters of the Gulf Stream and for constraining ocean simulations and forecasts in a region of complex topography. Existing transport time series of the inflow through Yucatan Channel and the outflow at 27°N yield a 9 Sv difference in the mean, which cannot be reconciled by the two minor inflows between. Here we present a synthesis of transport estimates from throughout the Florida Straits, using velocity data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Transport calculations from moorings suggest a considerable range of interannual transport variations (~5 Sv), higher than the one suggested by Rousset and Beal []. The AVISO‐120 transport proxy has a standard deviation of 1.2 Sv and a range of 4–5 Sv but recall this proxy underestimates the annual means of the CANEK transports.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Transport calculations from moorings suggest a considerable range of interannual transport variations (~5 Sv), higher than the one suggested by Rousset and Beal []. The AVISO‐120 transport proxy has a standard deviation of 1.2 Sv and a range of 4–5 Sv but recall this proxy underestimates the annual means of the CANEK transports.…”
Section: Discussionmentioning
confidence: 76%
“…Recent measurements (2001 to 2006) from shipboard acoustic Doppler current profiler (ADCP) through Yucatan Channel and Florida Straits suggest a ~30 Sv transport in both passages and a ~2.7 Sv seasonal variation [ Rousset and Beal , , , ]. These shipboard measurements combined with model data imply a small contribution (~3 Sv) from the OB and NWP channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current measurements show a northward‐flowing contour current at the east side of the SC and a weaker countercurrent at the margin of CSB (Leaman et al ., ; Lüdmann et al ., ). Approximately less than 2 × 10 6 m³ sec −1 of inflow enters the Florida Straits via the SC, fed by the OBC, with a strong subsurface current and a maximum speed at 300 m water depth (Rousset & Beal, ). The inflow of the subsurface water masses of the North Atlantic Central Water (Talley et al ., ) through the OBC is propelled by the thermohaline subtropical gyre and wind‐driven currents (Johns et al ., ).…”
Section: Regional Settingmentioning
confidence: 99%
“…The FC carries most of the waters of the Gulf Stream across 26 • N. The origins of this water come from the Yucatan Channel and Old Bahama Channel, across complex topography west of the Bahamas (Rousset and Beal, 2014). At similar latitudes, the flow through the Yucatan Channel has been found to compensate flow around Cuba (Lin et al, 2009), while variations in the FC have, at times, shown compensation east of the Bahamas in bottom pressure variations ) and in top 1000 m velocities (FrajkaWilliams et al, 2013).…”
Section: Umo and Fc Transports: Horizontal Circulationmentioning
confidence: 99%